Treatment of Ni-EDTA containing wastewater by electrocoagulation using iron scraps packed-bed anode. (December 2016) - Ye, Xiaokun; Zhang, Junya; Zhang, Yan; Lv, Yuancai; Dou, Rongni; Wen, Shulong; Li, Lianghao; Chen, Yuancai; Hu, YongYou
Abstract: The unique electrocoagulator proposed in this study is highly efficient at removing Ni-EDTA, providing a potential remediation option for wastewater containing lower concentrations of Ni-EDTA (Ni ≤ 10 mg L −1 ). In the electrocoagulation (EC) system, cylindrical graphite was used as a cathode, and a packed-bed formed from iron scraps was used as an anode. The results showed that the removal of Ni-EDTA increased with the application of current and favoured acidic conditions. We also found that the iron scrap packed-bed anode was superior in its treatment ability and specific energy consumption (SECS) compared with the iron rod anode. In addition, the packed density and temperature had a large influence on the energy consumption (ECS). Over 94.3% of Ni and 95.8% of TOC were removed when conducting the EC treatment at an applied current of 0.5 A, initial pH of 3, air-purged rate 0.2 L min −1, anode packed density of 400 kg m −3 temperature of 313 K and time of 30 min. SEM analysis of the iron scraps indicated that the specific area of the anode increased after the EC. The XRD analysis of flocs produced during EC revealed that hematite (α-Fe2 O3 ) and magnetite (Fe3 O4 ) were the main by-products under aerobic and anoxic conditions, respectively. A kinetic study demonstrated that the removal of Ni-EDTA followed a first-order model with the current parameters. Moreover, the removal efficiency of real wastewater was essentially consistent with that of synthetic wastewater. Highlights: A novel electrocoagulator with small gap between the electrodes was proposed. Iron scraps anode enhanced the Ni-EDTA removal comparing with iron rod anode. Adsorption ability of Fe(III) flocs was higher than that of Fe(II) flocs for Ni-EDTA. A large amount of active oligomeric ferric (Fe(O)) led to increased Ni-EDTA removal.